Teacher’s Verbal and Nonverbal Communication on Students’ Motivation in Learning English - Sophia, Luci; Rustandi, Andi; Sugiarto, Bambang Ruby (Journal of English Education Program (JEEP), 2024)
This study focuses on the teacher's verbal and nonverbal communication as well as the student's motivation in EFL classes. The goals of this study were to (1) assess the types of verbal and nonverbal communication used by teachers in EFL classrooms and (2) investigate how verbal and nonverbal communication influences students' motivation. The descriptive-qualitative method was utilized in this study. The research subjects were a teacher and 4 students selected from two classes in tenth-grade at MAN 3 Tasikmalaya. Data were gathered through observation (video recording) and interviews. The findings of this study revealed that the verbal type of FIACS and Schmitz has been fulfilled. There are the seven types of teacher verbal communication used in the classroom by the teacher. However, the researcher discovered that the most dominant type of teacher verbal communication is asking question in this study. In addition, the researcher engages in fourth sorts of nonverbal communication. Regarding the teacher's nonverbal communication, the researcher discovered that the most dominant type is kinesics such us body movement and gestures in this study. The findings also revealed that the teacher's verbal and nonverbal communication had a beneficial impact on their motivation to learn English. Positive effects include a sense of caring, a better understanding, a sensation of pleasure or comfort, an eagerness to learn, a sense of being appreciated and respected, as well as a sense of respect.